Bridging Climate Resilience and Financial Inclusion: The Role of Digital Financial Products in Flood-Affected Communities of North Bengal, Bangladesh - Mia, Md Rubel; Anderson, Chad David; Mahmud, Al; Dewan, Iman Ali; Islam, Md Jahirul (Quest Journal of Management and Social Sciences, 2025)
Background: Climate change has exacerbated the frequency and severity of flooding in Bangladesh, particularly in the North Bengal regions of Bogura and Kurigram. These floods disrupt livelihoods, exacerbate poverty, and pose long-term recovery challenges. Digital Financial Products (DFPs), such as mobile banking, micro-insurance, and mobile-based credit, are important facilitators of climate adaptation among the people suffering from the floods. The role of DFPs in improving financial inclusion and climate resilience in these vulnerable communities. Purpose: This study aims to assess the role and potential of DFPs in enhancing climate resilience among flood-affected communities to economic stability, disaster preparedness, and post-disaster recovery and improve financial inclusion in flood-prone areas. Methods: A purposive qualitative participatory rural appraisal (PRA) approach was employed using focus group discussions (FGDs), in-depth interviews (IDIs), and key informant interviews (KIIs) with stakeholders, including affected community members, local government officials, NGO representatives, and digital financial service providers. The study focuses on two flood-prone Upazilas: Sariakandi in Bogura and Nageshwari in Kurigram. Findings: The study reveals that people in the affected area are familiar with mobile banking, which ensures rapid and secure financial transactions, facilitating immediate access to remittances and emergency funds during crises. Benefits include receiving financial aid, immediate access to funds, lower-cost financial services, and reduction of risks. However, barriers such as the cost of maintaining reliable mobile service access, lack of digital literacy, lack of trust due to security concerns, and inadequate infrastructure hinder the widespread adoption of DFPs in flood-prone areas for climate resilience. These factors have led to a widespread recognition of DFP's potential but underutilisation in practice. Conclusion: While the benefits are consistent with the literature, they need further study as actual users were more concerned with aid and immediate access, non-users with lower costs, over the more common benefit in the literature of reduced risk. The potential of DFPs remains unrealised in rural Bangladesh due to several barriers that can be addressed by financial institutions, policymakers, and development agencies through education and digital literacy training, design of inclusive services, infrastructure expansion, and public support and use of DFPs that cater to the specific needs of vulnerable communities, thereby fostering sustainable climate resilience in North Bengal. Keywords: Digital Financial Products, Climate Change, Flood, Financial Inclusion, Bogura, Kurigram, Bangladesh. JEL Codes: O16, Q54, G21, D14